1988
DOI: 10.1210/endo-122-6-2933
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypervitaminosis A on the Bone and Mineral Metabolism of the Rat*

Abstract: Vitamin A toxicity has been associated with alterations in mineral metabolism and may result in osteopenia, fractures, deformities, and growth arrest. The pathogenesis of the bone lesions that occur in vitamin A toxicity is, however, ill defined and was examined in the present study. The administration of pharmacological doses of vitamin A to growing male rats resulted in weakness and spontaneous fractures. Undecalcified bone histology of vitamin A toxic animals was characterized by increased bone resorption, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 41 publications
2
78
0
1
Order By: Relevance
“…The protein is considered to be an indicator of osteoblast activity and is regarded as a marker of bone formation (20)(21)(22). Previous experimental studies have found that vitamin A hypervitaminosis decreases bone formation in rats (23), and that the retinol metabolite, retinoic acid, decreases production of alkaline phosphatase, osteocalcin, and interleukin-6 in human osteoblast cells, and simultaneously decreases differentiation of those cells (24). Thus, our results may indicate that retinol decreases bone formation in young men.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The protein is considered to be an indicator of osteoblast activity and is regarded as a marker of bone formation (20)(21)(22). Previous experimental studies have found that vitamin A hypervitaminosis decreases bone formation in rats (23), and that the retinol metabolite, retinoic acid, decreases production of alkaline phosphatase, osteocalcin, and interleukin-6 in human osteoblast cells, and simultaneously decreases differentiation of those cells (24). Thus, our results may indicate that retinol decreases bone formation in young men.…”
Section: Discussionmentioning
confidence: 51%
“…These results are of interest also with respect to the present study, since vitamin A has been suggested to antagonize vitamin D's positive influence on bone mineralization and calcium uptake (23,(36)(37)(38). We therefore also investigated whether levels of vitamin A and RBP-4 were associated with levels of vitamin D presented in a previous study (19).…”
Section: Discussionmentioning
confidence: 70%
“…Thus, there have been numerous animal studies demonstrating that a prolong excessive intake of vitamin A can cause ossification of cartilage, increased bone resorption, extraosseous calcification, hypercalcaemia, and suppressed parathyroid hormone levels [23][24][25]. More recently, there have been many cross-sectional studies (Table 3), which have compared the dietary intake of retinol and Bone Mineral Density (BMD).…”
Section: Toxicological Implications Of Elevated Hepatic Storage Of VImentioning
confidence: 99%
“…These observations suggest that retinal may be an additional vitamin A derivative that plays an important role as a mediator of biological processes. Hypervitaminosis A in experimental animals has been linked to increased bone resorption, decreased bone mass, and increased fractures [Frankel et al 1986, Hough et al 1988, Johansson et al 2002. There are also case studies in humans showing that significantly increased intake of vitamin A increases bone resorption, causes hypercalcemia, and induces skeletal pain [Frame et al 1974].…”
Section: Introductionmentioning
confidence: 99%